Shocking Germany: A spatial analysis of German regional labor markets - Oliver Krebs (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2018)
This paper quantifies the surprisingly large heterogeneity of real income and employment effects across German counties in response to local productivity shocks. Using a quantitative model with imperfect mobility and sector-specific labor market frictions together with an outstanding data set of county level goods shipments, I identify the sources of the heterogeneity in Germany's complex interregional linkages. I find that population mobility reduces the magnitude of local employment rate responses by a striking 70 percent on average. In all but a few counties, changes in the sectoral composition of production have a much milder effect on employment elasticities. National employment rates are less dependent on mobility with worker in- and outflows in individual counties partially cancelling out effects. For productivity shocks affecting individual sectors across all regions the composition effect is substantially magnified, the mobility effect reduced. In line with recent real world observations I find that real income and employment effects, while correlated, do not need to be of the same sign. Finally, the spatial propagation of real income effects closely follows trade linkages whereas employment effects are more complex to predict.
Keywords: F16; F17; R13; R23; 330; Quantitative spatial analysis; unemployment; migration; search and matching; labor market frictions